Experimental study on centrifugal concrete-filled steel tubes under bending and torsion - 金伟良 曲晨 于戈 (Journal of Zhejiang University. A. Science, 2003)
A real-size experiment on 11 tubes was done to study the performance of centrifugal concrete-filled steel tubes under bending and torsion. This paper first introduces the relevant operating method, equipment, subjects and processes. The factors that affect deformation and stiffness and the break mechanism under different loading were studied. Experimental stress analysis showed that the values of practical critical stress of steel tubes accorded well with the MISES Yielding Rule. The correlative equation (on the bearing capacity of a structural member under bending and torsion) deduced in this study may provide valuable reference for the desima of this structural member.